Xanthones from Calophyllum gracilipes and their cytotoxic activity. - Mad Nasir, Nadiah; Rahmani, Mawardi; Shaari, Khozirah; Kassim, Nur Kartinee; Go, Rusea; Stanslas, Johnson; Jeyaraj, Ethel Jeyaseela (Universiti Kebangsaan Malaysia, 2013)
Extraction and chromatographic isolation of the hexane, chloroform and methanol extracts of stem bark of Calophyllum gracilipes has led to the isolation of a new xanthone, gracixanthone (1) and the known zeyloxanthanone (2) and trapezifolixanthone (3) together with three common sterols, namely stigmasterol, friedelin and lupeol. The structures of the compounds were elucidated and established by spectroscopic analysis and compared with the spectral data from literature. The cytotoxicity of the compounds was evaluated and zeyloxanthanone (2) exhibited strong activity towards five cell lines with IC50 values ranging at 8.00-26.00μM.